Penanganan Tindak Pidana Jaminan Fidusia oleh Penyidik Kepolisian Daerah Sumatera Selatan - Ihsan, Muhammad; Burhayan, Burhayan (Kajian Ilmiah Hukum dan Kenegaraan, 2024)
Purpose: This study aimed to analyze the investigation of criminal acts related to fiduciary guarantees based on Article 36 of Law No. 42 of 1999 by the Directorate of Special Criminal Investigation of the South Sumatra Regional Police. Additionally, it examines the criminal aspects involving both the fiduciary giver and recipient under fiduciary guarantee law. Methodology/approach: This research was a normative legal study supported by empirical data obtained through field research relevant to the study’s topic. Results/findings: Police investigators investigated fiduciary givers who pawned, transferred, or leased fiduciary guarantee objects without the consent of the fiduciary recipient (creditor). The investigation results in a case file submitted to the public prosecutor. Such actions violate Article 36 of Law No. 42 of 1999 and are subject to a maximum penalty of two years’ imprisonment or a fine of up to IDR 50,000,000. Fiduciary recipients may also be criminally liable if they seize fiduciary objects without court authorization or enforce debt collection by force, potentially violating Articles 365 and 368 of the Indonesian Criminal Code. Conclusions: The investigation of fiduciary crimes begins with a report by the creditor as the victim. Violations by either the fiduciary giver or recipient may result in criminal sanctions, as stipulated by applicable laws. Limitations: This study is limited to the criminal law aspects of fiduciary guarantees and does not address civil law issues. Contribution: This research is expected to serve as a reference for law enforcement, academics, and the public to understand the criminal aspects of fiduciary guarantees.